Health on the Way to School: A Comparison of High-Risk Behaviors Among Students Across Different Modes of School Transportation - Firuz Jahantigh , Vahid; Sanagouye Moharer, Gholamreza; Fardin , Mohammadali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The manner in which students commute to school and its psychological implications have received limited attention from parents and psychologists. Although observational learning (modeling) during students’ daily journeys to and from school plays a significant role in shaping their behaviors and everyday learning experiences, relatively little research has been conducted in this area. The present study aimed to examine the tendency toward high-risk behaviors among secondary school students across different modes of school transportation.Methods and Materials: The present research employed an ex post facto (causal-comparative) design. The sample consisted of 360 students, including 180 female and 180 male students. Participants were selected using a combination of cluster and stratified sampling methods. Data were collected using the Iranian Adolescents Risk-Taking Scale (IARS) developed by Zadeh Mohammadi et al. (2011).Findings: The results of multivariate analysis of variance (MANOVA) indicated a statistically significant difference between school transportation methods and students’ tendencies toward high-risk behaviors. Except for two cases in which female students demonstrated higher mean scores than males on tendencies toward high-risk behaviors, male students generally exhibited higher mean scores across different school transportation methods. Female students reported higher mean scores for sexual relationships and sexual behaviors in the active transportation group compared to male students. Furthermore, female students demonstrated higher mean scores for relationships with the opposite sex in the family transportation group than their male counterparts. In addition, the mean tendency toward substance use was higher among students who used public transportation.Conclusion: Although students’ commuting patterns constitute an important component of their daily activities, peer and community modeling—whether positive or negative—also represents an inseparable aspect of every culture and remains a recurring concern for parents. Therefore, greater attention should be paid to this issue and its psychological effects on both female and male students.